2020
DOI: 10.1002/sctm.19-0209
|View full text |Cite
|
Sign up to set email alerts
|

Human fetal mesoangioblasts reveal tissue-dependent transcriptional signatures

Abstract: Mesoangioblasts (MABs) derived from adult skeletal muscles are well-studied adult stem/progenitor cells that already entered clinical trials for muscle regeneration in genetic diseases; however, the transcriptional identity of human fetal MABs (fMABs) remains largely unknown. Herein we analyzed the transcriptome of MABs isolated according to canonical markers from fetal atrium, ventricle, aorta, and skeletal muscles (from 9.5 to 13 weeks of age) to uncover specific gene signatures correlating with their peculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In line with Dominici et al [ 12 ], immunophenotypic characterization studies highlighted the negativity to hematopoietic markers (i.e., CD14 and CD45), as well as the positivity for stem cell markers such as CD73, CD105 and CD90. Similar to multipotent cells isolated from the perivascular niche [ 24 ], they were positive for CD34, as well as for markers typically expressed by pericytes [ 25 ], such as CD13 and NG2. Furthermore, the absence of MHC class II molecules (HLA-DR) expression suggests that CMCs transplantation may be connected to a low risk of immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In line with Dominici et al [ 12 ], immunophenotypic characterization studies highlighted the negativity to hematopoietic markers (i.e., CD14 and CD45), as well as the positivity for stem cell markers such as CD73, CD105 and CD90. Similar to multipotent cells isolated from the perivascular niche [ 24 ], they were positive for CD34, as well as for markers typically expressed by pericytes [ 25 ], such as CD13 and NG2. Furthermore, the absence of MHC class II molecules (HLA-DR) expression suggests that CMCs transplantation may be connected to a low risk of immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In muscle degenerative disease animal models, several studies have shown the intrinsic capacity of MABs to contribute to muscle regeneration (14)(15)(16)(17)(18). Recently it has been demonstrated that MABs derived from fetal tissues show high plasticity and elevate differentiation capabilities (19). In particular, transcriptional profiles of MABs derived from aorta, atrial, ventricular, and skeletal muscles of fetuses revealed that each subset of MABs displayed a set of differentially expressed genes, which seem to reflect their distinct tissue derivations.…”
Section: Introductionmentioning
confidence: 99%
“…However, when muscle loss becomes irreversible (e.g., in case of severe trauma, invasive surgeries, degenerative diseases, or because of aging), lesions are so critical that they impair muscle functionality (Young, 1964). In this scenario, muscle regenerative medicine can provide solutions (Langridge et al., 2021; Ronzoni et al., 2020).…”
Section: Introductionmentioning
confidence: 99%